Planning for multilingualism and minority language rights in Sweden - Hult, Francis (Springer, 2004)
As the presence of English in Europe continues to grow, there is a mounting interest in the position of national languages among European institutions, societies, and people. Swedish, like many national languages in Europe and throughout the world, is in an awkward position. It is at the same time a strong national language with the potential to dominate other languages within national borders and a potentially dominated language with respect to English as an international language. Sweden is currently faced with balancing this delicate position in its language policies. This paper explores recent developments in status planning, particularly with respect to language rights, for Sweden’s five recognized national minorities and their languages. Swedish minority language issues are situated in sociohistorical context and recent language policy initiatives are analyzed. It is suggested that Swedish policy trends are moving towards fostering societal multilingualism.